Optimizing the Processing Temperature for Synthesis of Silver Nanoparticles within Cellulose-Wool Keratin supramolecular Matrix using Butylmethylimmidazolium Chloride Ionic Liquid - Mushi , Ngesa Ezekiel (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">To date, the synthesis of silver nanoparticles on the surface of cellulose and wool keratin biopolymer, while dissolved in ionic liquid, is <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">attractive because of its biomedical potential. However, the optimal processing temperature for the nanoparticle formation is unclear. The previously reported temperature of approximately 120°C gives unpredictable results. The current study employs a combination of 50% cellulose and 50% keratin, along with 69 mg of silver chloride, in Butylmethylimidazolium Chloride BMImCl ionic liquid, using a singlepot process to produce a supramolecular film via non-derivatized mechanochemical interactions. The primary objective is to <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">experimentally establish the processing temperature to achieve stable growth of metallic silver nanoparticles. The synthesis was conducted by heating the ionic mixture at temperatures of 110°C, 120°C, and 130°C. The study observed that raising the temperature to around 130ºC for 5 min is more practical. Moreover, though this data is higher, it does not compromise the thermal stability of cellulose and keratin's structure. The structural properties of the nanoparticles have been confirmed using Fourier transform spectroscopy (FTIR) and scanning electron microscopy (SEM). Furthermore, energy-dispersive X-ray spectroscopy (EDS) and powder X-ray diffraction (XRD) provide valuable insights into the physical characteristics of the produced silver nanoparticles, with a diameter of around 8.5 nm, and are uniformly distributed in-plane within the matrix. While the underlying mechanisms remain uncertain, they likely involve anchoring ionic silver onto the wool keratin while dissolved within the ionic liquid at elevated temperatures before reducing to metallic silver at room temperatures. Besides being sustainable, this green approach enhances understanding of the possibility of creating stable silver nanoparticles within the supramolecular matrix, which is essential for future applications in the biomedical field